Deseo de la madre y función materna. Cuando no es infanticidio. - Mejía Tenepaguay, Kelly Yajaira (My University, 2019)
This essay tries to synthesize the importance of a correct theoretical management by the psychologist in the forensic field. Thus, within the judicial process there is the participation of a multidisciplinary group of professionals, the same ones that will seek from their science to establish an opinion that serves as an orientation for the judicial decision. Within this investigation the multiple truths about mother according to the different sciences are established. This definition is particularized from a psychoanalytical approach that can be used within a skill making relevance in concepts necessary for its understanding such as: maternal desire, female desire, maternal function, woman. Likewise, the methodology used in this work responds to a type of qualitative research that aims to elucidate the conception of motherhood from the psychoanalytic approach through the literature review of scientific articles and books that allow, through intra and extra-textual analysis, establish a theoretical support that explains the dynamics of a reality. The case proposed to complement the theory refers to the death of a newborn and presents the child's mother as guilty of this infanticide. As conclusions, it could be elucidated that the importance of a correct formation of the expert psychologist will prevent it from being evaluated with a biological orientation and, consequently, the information that could be provided from human subjectivity within a judicial process is contaminated.
Este ensayo pretende sintetizar la importancia de un correcto manejo teórico por parte del psicólogo en el ámbito forense. Es así que dentro del proceso judicial se da la participación de un grupo multidisciplinario de profesionales, los mismos que pretenderán desde su ciencia establecer un dictamen que sirva de orientación para la decisión judicial. Dentro de esta investigación se establecen las múltiples verdades sobre madre según las diversas ciencias. Se particulariza dicha definición desde un enfoque psicoanalítico que pueda ser usado dentro de una pericia haciendo relevancia en conceptos necesarios para la comprensión del mismo tales como: deseo materno, deseo femenino, función materna, mujer. Así mismo, la metodología usada en este trabajo responde a un tipo de investigación cualitativa que pretende dilucidar la concepción de la maternidad desde el enfoque psicoanalítico mediante la revisión bibliográfica de artículos científicos y libros que permitan, a través del análisis intra y extra-textual, establecer un sustento teórico que explique la dinámica de una realidad. El caso propuesto para complementar la teoría refiere la muerte de un neonato y presenta como culpable de este infanticidio a la madre del menor. Como conclusiones se pudo dilucidar que la importancia de una correcta formación del perito psicólogo evitará que se evalúe con orientación biologicista y, por consiguiente, se contamine la información que se podría aportar desde la subjetividad humana dentro de un proceso judicial.
Keywords: DESEO FEMENINO; DESEO MATERNO; MADRE; PSICOANALISIS